Dapur Kita Project: Students Helping Students - Nor Azlina, Ahmad (UMPSA, 2024)
PEKAN, 13 January 2024 – A total of 300 pieces of roti canai and 600 pieces of pancakes were successfully distributed to students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) through the Dapur Kita (Our Kitchen) initiative with the 'Students Helping Students' approach.